2014
DOI: 10.1073/pnas.1319779111
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and visualizing cell phenotype differences from microscopy images using transport-based morphometry

Abstract: Modern microscopic imaging devices are able to extract more information regarding the subcellular organization of different molecules and proteins than can be obtained by visual inspection. Predetermined numerical features (descriptors) often used to quantify cells extracted from these images have long been shown useful for discriminating cell populations (e.g., normal vs. diseased). Direct visual or biological interpretation of results obtained, however, is often not a trivial task. We describe an approach fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
139
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(145 citation statements)
references
References 17 publications
(26 reference statements)
1
139
0
Order By: Relevance
“…We hypothesize that transforming MRI data using the new TBM approach can facilitate both discovery as well as visualization of discriminating differences in a manner similar to 1D and 2D signal analysis previously reported [13, 14, 15, 16, 17, 18, 19]. Ultimately, the goals of discovering objective clinical markers and understanding structure-function relationships would be facilitated by a technique that could assess structural changes underlying clinical phenotype in a fully automated manner without information loss and visualize the shifts in tissue distribution as a series of radiology images as part of a unified framework.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…We hypothesize that transforming MRI data using the new TBM approach can facilitate both discovery as well as visualization of discriminating differences in a manner similar to 1D and 2D signal analysis previously reported [13, 14, 15, 16, 17, 18, 19]. Ultimately, the goals of discovering objective clinical markers and understanding structure-function relationships would be facilitated by a technique that could assess structural changes underlying clinical phenotype in a fully automated manner without information loss and visualize the shifts in tissue distribution as a series of radiology images as part of a unified framework.…”
Section: Introductionmentioning
confidence: 88%
“…As previous work has demonstrated that transforming signals to the transport domain using OMT may increase their separability [13, 14, 15, 16, 17, 18, 19], we describe a framework for regression, discrimination, and blind signal separation in the transport space.…”
Section: Modeling Shape and Appearance Of The Brainmentioning
confidence: 99%
See 3 more Smart Citations